Function of Platelet-Induced Epithelial Attachment at Titanium Surfaces Inhibits Microbial Colonization. (June 2017) - Maeno, M.; Lee, C.; Kim, D.M.; Da Silva, J.; Nagai, S.; Sugawara, S.; Nara, Y.; Kihara, H.; Nagai, M.
The aim of this study was to evaluate the barrier function of platelet-induced epithelial sheets on titanium surfaces. The lack of functional peri-implant epithelial sealing with basal lamina (BL) attachment at the interface of the implant and the adjacent epithelium allows for bacterial invasion, which may lead to peri-implantitis. Although various approaches have been reported to combat bacterial infection by surface modifications to titanium, none of these have been successful in a clinical application. In our previous study, surface modification with protease-activated receptor 4–activating peptide (PAR4-AP), which induced platelet activation and aggregation, was successful in demonstrating epithelial attachment via BL and epithelial sheet formation on the titanium surface. We hypothesized that the platelet-induced epithelial sheet on PAR4-AP–modified titanium surfaces would reduce bacterial attachment, penetration, and invasion. Titanium surface was modified with PAR4-AP and incubated with platelet-rich plasma (PRP). The aggregated platelets released collagen IV, a critical BL component, onto the PAR4-AP–modified titanium surface. Then, human gingival epithelial cells were seeded on the modified titanium surface and formed epithelial sheets. Green fluorescent protein (GFP)–expressing Escherichia coli was cultured onto PAR4-AP–modified titanium with and without epithelial sheet formation. While Escherichia coli accumulated densely onto the PAR4-AP titanium lacking epithelial sheet, few Escherichia coli were observed on the epithelial sheet on the PAR4-AP surface. No bacterial invasion into the interface of the epithelial sheet and the titanium surface was observed. These in vitro results indicate the efficacy of a platelet-induced epithelial barrier that functions to prevent bacterial attachment, penetration, and invasion on PAR4-AP–modified titanium.